Time-differentiated pricing and direct load control of residential electricity consumption - Torgeir Ericson (Statistics Norway, Research Department, 2006)
Time-of-use and real-time spot pricing tariffs in conjunction with direct load control of water heaters was offered to residential electricity consumers in a large-scale demand response experiment. Hourly data from the experiment on consumption, temperature, wind, and hours of daylight comprise a large panel data set, which are analysed with a fixed effects regression model. Price responses are estimated for three customer groups, which differ with respect to their choices of tariffs and requests for direct load control. The results indicate differing responses between the groups depending on their tariff combination.
Keywords: D10; Q41; 330; Time-differentiated pricing; TOU; direct load control